You know what I mean! Idiosyncratic cueing supports older couples' communication efficiency - Rauers, Antje; Schmiedek, Florian; Lindenberger, Ulman; Riediger, Michaela (Frontiers in Developmental Psychology, 2025)
Collaborating with others on cognitive tasks may allow individuals to perform better than when working alone. Therefore, researchers have argued that collaborative cognition may help individuals compensate for age-related cognitive decline. However, interacting with others also poses cognitive demands that become more challenging with aging. This study examined an interpersonal resource that can ease this quandary: familiar partners' spontaneous use of idiosyncratic cues in a communication-efficiency task. Idiosyncratic cues are references to the previously established, shared knowledge of familiar partners. The usage of such cues might alleviate cognitive load to a greater extent than references to generic knowledge. We therefore hypothesized that older adults' communication efficiency would be particularly enhanced with the use of idiosyncratic cues. Thirty-eight younger couples (76 individuals, Mage = 26.64 years) and forty older couples (80 individuals, Mage = 71.59 years) collaborated on a communication-efficiency task based on the game Taboo©. Partners explained target words to each other, using as few words as possible. A total of 1,763 cueing episodes were transcribed and content-coded for idiosyncratic cues (intraclass correlation = 0.91). Multilevel regression models showed that communication efficiency was enhanced with more idiosyncratic cueing in older, but not younger couples. However, the interaction effect between age group and idiosyncratic cueing was not statistically significant. When the analyses were repeated in a subsample of difficult target words, both age groups profited from idiosyncratic cueing. These results suggest that personally tailored cues based on shared knowledge may facilitate everyday communication if task demands are high—a resource situation that becomes more likely as people age.